Game-related statistics for distinguishing winning and losing teams in Olympic basketball: The impact of game pace - Chen, R.; Zhang, M.; Xu, X.; Liu, Y. (Journal of Sports Sciences, 2024)
The pace of play, a critical tactical element in basketball, significantly influences offensive and defensive strategies. This study aimed to identify statistical indicators that differentiate winners from losers across varying game paces using a sample of 90 Olympic men`s basketball games from 2016, 2021, and 2024. Games were categorized as fast-paced or slow-paced via clustering algorithms. Stepwise Discriminant Analysis (SDA) identified key performance metrics, while an Exhaustive CHAID decision tree (E-CHAID) simulated outcomes based on game statistics. In fast-paced games, defensive rebounds (SC = 0.403), three-point field goals made (SC = 0.329), and free throws made (SC = 0.305) were crucial for distinguishing winners. In contrast, slow-paced games highlighted the importance of defensive rebounds (SC = 0.513), pick-and-roll ball-handler field goals missed (SC = -0.388), and cut field goals made (SC = 0.325). The decision tree further emphasized the significance of off-screen field goals made and steals as pivotal metrics. These findings offer insights into how game pace shapes performance indicators, providing strategic guidance for optimizing team tactics. By linking game statistics with match outcomes, this study contributes to understanding developmental trends in competitive basketball and enhancing technical and tactical performance.